Changes of cerebrospinal fluid pressure gradient in different body positions under experimental impairment of cerebrospinal fluid pathway: new insight into hydrocephalus development - Jurjević, Ivana; Orešković, Darko; Radoš, Milan; Brgić, Klara; Klarica, Marijan (Frontiers in Molecular Neuroscience, 2024)
It is generally accepted that hydrocephalus is a consequence of the disbalance between cerebrospinal fluid (CSF) secretion and absorption which should in turn lead to CSF pressure gradient development and ventricular enlargement. To test CSF pressure gradient role in hydrocephalus development, we experimentally caused CSF system impairment at two sites in cats. In the first group of animals, we caused Sylvian aqueduct obstruction and recorded CSF pressure changes pre and post obstruction at three measuring sites (lateral ventricle -LV, cortical-CSS and lumbar subarachnoid space -LSS) during 15 min periods and in different body positions over 360 degrees. In the second group of experiments, we caused cervical stenosis by epidural plastic semiring implantation and monitored CSF pressure changes pre and post stenosis implantation at two measuring sites (lateral ventricle and lumbar subarachnoid space) during 15 min periods in different body positions over 360 degrees. Both groups of experimental animals had similar CSF pressures before stenosis or obstruction at all measuring points in the horizontal position. During head-up verticalization, CSF pressures inside the cranium gradually became more subatmospheric with no significant difference between LV and CSS, as they are measured at the same hydrostatic level, while CSF pressure inside LSS became more positive, causing the development of a large hydrostatic gradient between the cranial and the spinal space. With cervical stenosis, CSF pressure inside the cranium is positive during head-up verticalization, while in cats with aqueductal obstruction CSF pressure inside the CSS remains negative, as it was during control period. Concomitantly, CSF pressure inside LV becomes less negative, thus creating a small hydrostatic gradient between LV and CSS. Since CSF pressure and gradient changes occur only by shifting body position from the horizontal plane, our results indicate that cervical stenosis in a head-up vertical position reduces blood perfusion of the whole brain, while aqueductal obstruction impairs only the perfusion of the local periventricular brain tissue. It seems that, for evolutionary important bipedal activity, free craniospinal communication and good spinal space compliance represent crucial biophysical parameters for adequate cerebral blood perfusion and prevention of pathophysiological changes leading to the development of hydrocephalus.